2010
DOI: 10.1007/s10295-010-0791-9
|View full text |Cite
|
Sign up to set email alerts
|

The apoptosis-inducing activity towards leukemia and lymphoma cells in a cyanobacterial culture collection is not associated with mouse bioassay toxicity

Abstract: Cyanobacteria (83 strains and seven natural populations) were screened for content of apoptosis (cell death)-inducing activity towards neoplastic cells of the immune (jurkat acute T-cell lymphoma) and hematopoetic (acute myelogenic leukemia) lineage. Apoptogenic activity was frequent, even in strains cultured for decades, and was unrelated to whether the cyanobacteria had been collected from polar, temperate, or tropic environments. The activity was more abundant in the genera Anabaena and Microcystis compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Several studies have shown that cyanobacteria produce a great number of diverse apoptosis inducing compounds effective against leukemia cells [70,77,79,82,106]. The new unpublished results are in line with our previous findings [70,77,82] showing divergent and high amount of apoptotic activities (Fig.…”
Section: Summary Of the New Data Included In The Studysupporting
confidence: 90%
See 1 more Smart Citation
“…Several studies have shown that cyanobacteria produce a great number of diverse apoptosis inducing compounds effective against leukemia cells [70,77,79,82,106]. The new unpublished results are in line with our previous findings [70,77,82] showing divergent and high amount of apoptotic activities (Fig.…”
Section: Summary Of the New Data Included In The Studysupporting
confidence: 90%
“…A particular advantage with cell assays is that these are compatible with different types of samples, ranging from crude extracts to HPLC-fractions, or purified compounds. A selection of a few cell lines is often chosen to screen a whole culture collection [79][80][81][82] and selected extracts or purified compounds are scrutinized for anticancer effect on a large panel of cancer and normal cell lines [70,83] often combined with chemical analyses of extract to find the compound of interest [84].…”
Section: Cell-based Assaysmentioning
confidence: 99%
“…Apoptosis leads to characteristic changes (morphology) and death of cells [26]. Cyanobacterial extracts have been found to contain long acting apoptotic compounds [10]. Research demonstrated that Oscillatoria terebriformis extract reduced cell viability of Human Lung Cancer Cell Lines by induction of apoptosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cyanobacterium Cyanothece sp. had high anticancer effect on extracellular T-lymphoma cells [10].…”
Section: Introductionmentioning
confidence: 98%
“…These toxins do not distinguish between malignant and nonmalignant cells if microinjected into the cells [62]. Nevertheless, previous studies have shown that there is no correlation between phosphatase inhibitors and apoptogenic activity against SH-SY5Y-neuroblastoma and AML cells [58,63]. The lipopeptides hassallidin and puwainaphycin have been previously shown to have cytotoxic activity [64,65].…”
Section: Discussionmentioning
confidence: 99%